International Human Rights Protection Mechanisms Based on the Ideas of H. Lauterpacht - Sheredko, Olga (Teisė, 2023)
The Article aims at revealing the ideas of Hersch Lauterpacht on the mechanism of human rights protection that can be found in today’s international mechanisms for safeguarding human rights. Analysis covers the idea of an international body suggested by H. Lauterpacht that was aimed to provide the observance of fundamental human rights and freedoms. The research involves a comparison of the human rights protection mechanism proposed by H. Lauterpacht and the current mechanisms on both universal and regional (European) levels.
Keywords: international law; human rights; H. Lauterpacht; Universal Declaration of Human Rights; mechanism for protection of human rights